2010
DOI: 10.4025/actasciagron.v32i4.5282
|View full text |Cite
|
Sign up to set email alerts
|

Test procedure for variable rate fertilizer on coffee

Abstract: ABSTRACT. The objective was to develop and test a procedure for applying variable rates of fertilizers and evaluate yield response in coffee (Coffea arabica L.) with regard to the application of phosphorus and potassium. The work was conducted during the 2004 season in a 6.4 ha field located in central São Paulo state. Two treatments were applied with alternating strips of fixed and variable rates during the whole season: one following the fertilizing procedures recommended locally, and the other based on a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 10 publications
0
17
0
13
Order By: Relevance
“…O termo agricultura de precisão (AP) é relativamente novo entre os produtores rurais brasileiros e tem gerado dúvidas na utilização de suas técnicas de manejo. Vários são os produtores que associam a AP como um pacote de metodologias que poderá solucionar todos os problemas da agricultura nacional (MOLIN et al, 2010).…”
unclassified
“…O termo agricultura de precisão (AP) é relativamente novo entre os produtores rurais brasileiros e tem gerado dúvidas na utilização de suas técnicas de manejo. Vários são os produtores que associam a AP como um pacote de metodologias que poderá solucionar todos os problemas da agricultura nacional (MOLIN et al, 2010).…”
unclassified
“…Silva et al (2007;2008) and Ferraz et al (2012) characterized the spatial variability of soil chemical attributes in the coffee crop and the studied variables showed structure of spatial dependence; these authors also observed that, with great variation amplitude of chemical attributes, the differential and localized application of fertilizers in the coffee crop is justified. Molin et al (2010), in a study comparing applications at variable and fixed rates in the coffee crop, observed that the area where the fertilizers were applied in variable rates showed a 34% yield increase, in comparison to the area under the application of fixed rates. Ferraz et al (2011) observed that manual application of variable rates of phosphorus and potassium was economically more advantageous, in comparison to the conventional application system.…”
Section: Introductionmentioning
confidence: 99%
“…Precision agriculture (PA) is an agricultural management system based on spatial variations of soil and crops attributes in production fields. PA aims to optimize profitability, sustainability and environmental protection (MOLIN et al, 2010) by employing localized application of inputs to an agricultural field. Among studies seeking to evaluate the economic viability of PA, those that incorporate management zones (MZs) aim to analyze and provide recommendations on the division of production areas into smaller MZs that are treated differently.…”
Section: Introductionmentioning
confidence: 99%